A Descriptive Review on Applied Linguistics and Educational Linguistics - Khafidhoh, Khafidhoh (Ahmad Dahlan Journal of English Studies, 2015)
Both of applied linguistics and educational linguistics are almost the same but they are actually different. By having knowledge about them, one can differentiate and make relationship between them. This article aims at giving a descriptive review on applied linguistics and educational linguistics. The topics covered in this article are the definitions of the applied linguistics and educational linguistics, the relationship, the similarity and the difference between them, and also the scope of each of the two disciplines. Keywords: applied, educational, linguisticsÂ